THE EMERGENCE OF "MOVEMENT PEDAGOGY" OF THE PEOPLE AFFECTED BY DAMS - Sérgio Roberto Moraes Corrêa; Severino Bezerra da Silva (Editora da Universidade de Santa Cruz do Sul, 2016)
This text is part of a master's dissertation research defended in the Graduate Education Program of the UFPB. This research had a qualitative approach involving bibliographic research, documentary and field. The locus of the research was the municipality of Tucuruí, in the State of Pará, where was built the hydropower's Tucuruí, one of the biggest model of development projects conservative, that produced great social and environmental impacts and caused the emergence of social resistance movements, as the MAB. as cropping, this text proposes to analyze the proposal of Movement Education of People Affected by the hydropower. (MAB) as a result, it is verified that this education proposal expressed the emergence of an Pedagogy Movement of Peoples Affected by Dam, which positions itself at a critical field and counter-hegemonic.